STUDY OF WAVE PROPAGATION WI-FI IN ROOM - Конахович, Г. Ф.; Хомяк, В. В; Тищук, С. M.; Пасічник, В. М.; Кичигіна, М. Д. (Science-based technologies, 2010)
An investigation of the quality of connection with the usage of WiFi technology so through the presence of obstacles depending on the angel of location of users is represented Recommendation to the net organizations in the office-room are suggested.